IMPLEMENTASI PENDAYAGUNAAN ZAKAT DALAM PENGEMBANGAN EKONOMI PRODUKTIF DI LAZISMU KABUPATEN DEMAK JAWA TENGAH TAHUN 2017 - Shobron, Sudarno; Masruhan, Tafrihan (Profetika Jurnal Studi Islam, 2017)
Zakah is a treasure worship that is believed to be able to overcome social and economic problems. Not just to meet the basic needs of the mustahiq Zakat has the ability to develop people's economy. To get the maximum results zakat institutions need to do a lot of new studies and breakthroughs. Lazismu of Demak utilizes zakat for the development of productive economy with the goal of creating jobs, reducing unemployment and poverty. This is what makes researchers interested in conducting research to find out what kind of zakah implementation in the development of productive economy as well as the economic development mustahik after the implementation of zakat as a productive economy. Because it includes field research researchers used the Phenomenological approach data collected through observation, documents,questionnaires and interviews. Then, the data was analyzed sequentially and interactively consisting of three stages, namely: 1) data reduction, 2) data presentation, 3) conclusion drawing or verification. The productive use of zakat in developing productive economy consisted of traditional and creative uses. Traditional economic productive use was realized by providing working tool to mustahiq. Creative economic productive was conducted by providing capital in from of pure grant to mustahiq, provide a capital loan in a very easy way, not burdening the mustahiq and invest zakat funds into the real business sector. The zakat institution will receive capital invested and benefit from the businesses, then the capital and benefits will be used for ummah advantages. From the findings, it can be known that some participants of productive economy were able to develop their business well. Some others were only able to meet their basic daily needs. While some more others were less trustworthy in using capital loan provided.Zakat adalah  ibadah maliyah yang mampu mengatasi masalah-masalah sosial dan ekonomi. Selain memenuhi kebutuhan pokok para mustahiq, zakat mampu mengembangkan perekonomian ummat. Untuk mendapatkan hasil maksimal tersebut, lembaga-lembaga zakat perlu banyak melakukan kajian dan terobosan-terobosan baru. Seperti LAZISMU Demak yang mendayagunakan zakat untuk pengembangan ekonomi produktif dengan tujuan  menciptakan lapangan pekerjaan, mengurangi pengangguran serta  kemiskinan.  Inilah yang mendorong diadakannya penelitian guna mengetahui seperti apa implementasi pendayagunaan zakat dalam pengembangan ekonomi produktif serta perkembangan ekonomi mustahiq setelah diimplementasikannya zakat sebagai ekonomi produktif. Karena termasuk  penelitian lapangan (field research), peneliti menggunakan pendekatan Phenomenologis, data dikumpulkan melalui     observasi, dokumen, angket dan wawancara, kemudian  akan dianalisis secara berurutan dan interaksionis yang terdiri dari tiga tahap, yaitu: 1) Reduksi data, 2) Pernyajian data, 3)  Penarikan simpulan atau verifikasi.  Dari penelitian tersebut didapatkan hasil  bahwa bentuk pengembangan ekonomi produktif di LAZISMU DEMAK meliputi tradisional dan kreatif. Ekonomi  produktif  tradisional meliputi pembelian  alat kerja untuk mustahiq. Adapun ekonomi produktif kreatif melaui pemberian modal dalam bentuk hibah murni, memberikan pinjaman modal dengan cara yang sangat mudah, tidak membebani mustahiq dan menginvestasikan dana zakat ke sektor usaha nyata. Hasil investasi dimanfaatkan sebesar-besarnya untuk mustahiq. Dengan cara ini sebagian peserta ekonomi produktif mampu mengembangkan usahanya dengan baik, sebagian lagi hanya mampu  memenuhi kebutuhan pokok sehari-hari dan sisanya  kurang amanat dalam menggunakan pinjaman modal yang diberikan.